Solvent-Free Synthesis of a Superamphiphobic Surface by Green Chemistry - Ozbay, Salih; Cengiz, Ugur; Erbil, H. Yildirim (Amer Chemical Soc, 2019)
A superamphiphobic surface having both water and oil repellence was prepared by applying a solvent-free surface coating method using liquid-CO2 in the scope of green chemistry. Poly(perfluoroalkyl ethyl acrylate) homo- polymer was synthesized by a free radical polymerization in supercritical CO2 medium. This polymer was dissolved in liquid-CO2 containing hydrophilic nanosilica particles in a stirred stainless steel reactor at room temperature under a low CO2 pressure. The polymer/nanosilica dispersion was used to coat glass slides located horizontally in a stainless steel tube by using the free meniscus coating method. A series of superamphiphobic coatings were formed under different coating conditions with the variation of polymer/nanosilica concentrations, the types of nanosilica powders, system pressures, and degassing flow rates. The highest apparent water contact angle was 173 degrees and the hexadecane contact angle was 169 degrees on these superamphiphobic hybrid coatings with roll-off angles that were <7 degrees. Such superamphiphobic surfaces have a large potential in biomedical applications for the preservation of small amounts of bioliquids during analysis. In a parallel study, a superhydrophobic surface without containing any nanosilica powder was also obtained by applying the rapid expansion supercritical solution method. Polyperfluoroacrylate polymer was dissolved in supercritical CO2 and was sprayed onto glass slides that were previously coated with a polyacrylate adhesive layer. The water contact angles were larger than 170 degrees on this superhydrophobic coating. To optimize the coating conditions, the cloud point pressures of polyperfluoroacrylate polymer in sc-CO2 were determined at various polymer concentrations and temperatures for this purpose.
Keywords: superamphiphobic; superhydrophobic; free meniscus coating; liquid-CO2; RESS; cloud point